COLLABORATIVE ART ACTIVITY FOR YOUNG CHILDREN AND PARENTS: A SYSTEMATIC REVIEW - Juprachakorn, Narisorn; Sangvanich, Khanobbhorn (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: This article presents a systematic review of collaborative art activities for young children and their parents. The research questions are as follows: 1) What is the significance of cooperative learning between young children and their parents? 2) What skills should quality art activities promote for early childhood development? Methods: The criteria for selecting research articles are as follows: 1) Published research articles from 2014 to 2023. 2) Appeared in six online databases, both domestically and internationally, namely SCOPUS, Proquest, SAGE, ERIC, Thaijo, and Researchgateway. 3) Articles must be published in Thai and English; and 4. The samples are limited to preschool children. Key Findings: According to these selection criteria, a total of 15 articles addressing the research questions were gathered, which can be summarized as follows: 1) The importance of co-learning between young children and their parents is in fostering holistic development, which includes physical, emotional, social, and cognitive aspects. 2) Quality art activities should encourage young children to develop the following skills: (1) Imagination and creativity; (2) Language and literacy skills; (3) Emotional development and happiness; (4) Social development; (5) Awareness of nature conservation; and (6) Fine motor skills. Implications of the Study: This study underscores the critical importance of collaborative learning between young children and their parents, particularly through engagement in art-based activities. Such interactions significantly contribute to children’s holistic development—encompassing physical, emotional, social, and cognitive domains. While much of the existing literature tends to focus on activities conducted individually or among peers of the same age group, the role of parents in shared learning remains notably underexplored. This highlights a pressing need to expand the body of knowledge in this area. Moreover, high-quality art activities should be designed to cultivate a wide range of developmental skills, including creativity, language, emotional intelligence, social awareness, environmental consciousness, and fine motor coordination. These findings suggest that activity design must be responsive to the needs of both children and their parents. Additionally, in times of crisis such as the COVID-19 pandemic, the integration of technology and online platforms becomes crucial in strengthening family bonds and facilitating meaningful interaction within the home environment. Conclusions and Future Study: This systematic review highlights that most research on early childhood development usually focuses primarily on activities that children engage in playing independently or playing with peers of the same age group, overlooking the important role of parental involvement. Researches promoting collaborative learning between children and parents from 2014 to 2023 are still limited, indicating a significant gap in the literature. Thus, further research is needed to explore the essential role that parents play in enhancing young children's development through collaborative activities. To strengthen this research, it is important to include a broader range of foreign databases, which would provide a more comprehensive understanding of the topic, and incorporate deeper definitions and frameworks to address intergenerational relationships. Additionally, utilizing diverse knowledge sources can lead to innovative approaches to studying parent-child collaboration. This systematic review emphasizes that collaborative learning between young children and their parents is not just beneficial but essential for nurturing development across multiple domains, including physical, cognitive, and emotional growth. In the context of the COVID-19 pandemic, one effective solution for parents is to utilize online programs that are specifically designed to promote engaging activities while also enhancing communication with their children. Such programs can help improve communication and interaction between parents and children. Furthermore, it is imperative to prioritize family relationships, address parents' needs, support artistic development, and recognize the importance of play. These elements should serve as foundational guidelines for designing activities that actively strengthen the connections between young children and their parents, fostering a collaborative learning environment that is conducive to holistic development.